Penyelesaian Sengketa dalam Perjanjian Pembiayaan Konsumen sebagai Akibat Wanprestasi - Meita Djohan Oelangan (PRANATA HUKUM, 2012)
Defrayal agreement represent one of the way of to get required goods where buyer unable to pay for goods price cashly. Agreement like this non meaning do not contain risk. Risk will emerge if consumer do wanprestasi. Problem of research is how solving of dispute between the parties as effect of existence of wanprestasi. Strive the Solving of in the event of dispute because effect of wanprestasi use systems " handling procedure to consumer have problem" which is divided become eight solution time step. In the event of problems related to yuridis punish hence company peculiarly need legal attendance which showed by management. But in principle each;every resulted from by problems is consumer finished familiarityly and if cannot be delivered to body authority or justice. As suggestion institute defrayal of consumer shall be more be selective so that do not experience of loss of consumer effect doing wanprestasi.